β-Sitosterol Compound from Dichloromethane Extracts of Kalanchoe tomentosa (Crassulacea) Leaves and Inhibition of α-amilase Activity - Lilis Siti Aisyah; Yenny Febriani Yun; Firidia Puspita; Adelia Ilfani (Jurnal Kimia Valensi, 2021)
Kalanchoe tomentosa is one of the plants of the Crassulaceae tribe that can lower blood sugar and contains compounds of terpenoids, flavonoids, alkaloids, saponins, tannins, fatty acids, steroids, and triterpenoids. This study aims to isolate and identify chemical compounds from dichloromethane extract of Kalanchoe tomentosa leaves, as well as to test the inhibitory activity of the α-amylase enzyme. Extraction was carried out by maceration using dichloromethane as a solvent, then dichloromethane extract was purified using column chromatography, the pure isolate  was obtained in the form of white powder, and an inhibition test was carried out against the α-amylase enzyme. The thin layer chromatography data of pure isolates compared to pure β-sitosterol are similar. Based on the research data, it can be concluded that the chemical structure of the pure isolate is β-sitosterol, the methylene chloride extract of K. tomentosa leaves has an inhibitory activity against the α-amylase enzyme with an inhibition value of 65%. This value is greater than the positive control of acarbose which only has 37% inhibition and β-sitosterol compound by 6.7%. This value is smaller when compared to the control of acarbose at the same concentration which obtained 5% inhibition.